Uji Validitas Bahan Pengayaan Praktikum Fisiologi Tumbuhan sebagai Alat Pembelajaran - Fitri, Eliys Meisyah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to test the validity of enrichment materials for Plant Physiology practicals as a learning tool. The type of this research is development research. The development model used is the 4D model from Thiagarajan et al. (1974), but in this study, it has been modified to 3D. This study involves three expert validators who assess the content/material, appearance, and language aspects of the developed Plant Physiology practical enrichment materials. The research instrument used is a validation sheet. The data analysis technique uses the percentage technique. The validation results show that the enrichment materials for the Plant Physiology practical meet high validity criteria. The results of the content/material expert validation from the first validator obtained a score of 75%, the appearance expert validation from the second validator obtained a score of 81.25%, and the language expert validation from the third validator obtained a score of 96.88%. Based on these results, the enrichment materials for Plant Physiology practicals are declared valid and suitable for use as enrichment materials in the Plant Physiology course on the topic of Phytohormones. This research contributes to the development of teaching materials that can enhance the quality of learning in the field of Plant Physiology.